2018
DOI: 10.1111/ijac.13065
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical study of Fe3+‐doped Al2O3 nanocrystals prepared by new sol gel precursors

Abstract: Pure and Fe-doped Al 2 O 3 nanoparticles (NPs) were synthesized with different iron doping percentage of 1, 3, and 5 mol% employing sol gel technique with AlCl 3 , FeCl 3 as well as ethylene glycol (EG) and Polyvinylpyrrolidone (PVP) stabilizers as precursors. The XRD results indicated that the hexagonal structure of Fe/Al 2 O 3 nanocomposite with alpha phase was formed by the substitution of Fe 3+ ions in the alumina network. The sizes of the NPs obtained for the pure samples and doped samples at percentage d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…28 These observations are in line with the results for Fe-doped nanocrystals or nanoparticles, 12 in which dopant Fe atoms preferably replace Al atoms of the Al 2 O 3 network mostly in the surface layer 21 without inducing major distortions or even structural changes. 53 While structural deviations from the corresponding all-Al clusters are evident for the clusters with larger Fe : Al ratios ( n = 1–3), starting from Al 8 M O 13 + the cluster framework is virtually identical for M = Fe and Al, proving the suitability of iron as a dopant for Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 94%
“…28 These observations are in line with the results for Fe-doped nanocrystals or nanoparticles, 12 in which dopant Fe atoms preferably replace Al atoms of the Al 2 O 3 network mostly in the surface layer 21 without inducing major distortions or even structural changes. 53 While structural deviations from the corresponding all-Al clusters are evident for the clusters with larger Fe : Al ratios ( n = 1–3), starting from Al 8 M O 13 + the cluster framework is virtually identical for M = Fe and Al, proving the suitability of iron as a dopant for Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 94%
“…In 2013 Shaker and his colleagues obtained sol gel magnetic nanoparticles (Fe3O4) technique and showed that the crystallinity was improved at a higher treatment temperature and therefore the particle agglomeration decreased dramatically [11]. Khodadadi and his colleagues developed sol-gel method of Al2O3 nanocrystals and Fe-doped Al2O3 nanocrystals [12]. Sun and his associates successfully reported soluble gel-soluble ZnO thin films at a relatively low temperature (≤200 °C), which can function as an efficient transport layer in inverted solar cells [13].…”
Section: M-or + Ho-m = M-o-m + R-oh M-oh + Ho-m = M-o-m + Ho-hmentioning
confidence: 99%
“…Due to its stable thermodynamics, it is considered α-Alumina Oxide (α-Al 2 O 3 /corundum) one of the most important phase, α-Al 2 O 3 has a variety of applications, including ceramic, high-strength materials, transparent armor for ballistic performance, catalysts, catalyst support, adsorbents, and electronic matching like high-performance Field Effect Transistors (FETs), optoelectronics, electrical insulators, thermoluminescent dosimeters, light-emitting display, cutting tools, lasers, spark plugs, and gas sensor 1 , 3 – 5 . α-Al 2 O 3 is formed at temperatures above 1100 °C, with a hexagonal crystalline structure and lattice parameters a = 4.758 Å and c = 12.991 Å 6 , 7 . (α-Al 2 O 3 ) has direct energy transition and energy gap (E g ) 4.116 eV 5 8.8 eV 8 .…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies that prepared pure α-Al 2 O 3 and doped with some metallic elements, but the prepartion of pure α-Al 2 O 3 as nanocomposite with copper oxide or vanaduim oxide was scarce,and from this point we sought to prepare pure α-Al 2 O 3 , α-,Al 2 O 3 /CuO(AC) and α-Al 2 O 3 /V 2 O 5 (AV) as a nanocomposite to improve the properties and search for its uses in many other applications. There are many methods used to prepare oxides as pure and nanocomposite materials, such as sol gel 5 , 6 hydrothermal 12 , Co 2 laser vaporization 2 , physical vapro deposition(PVD) 13 ….etc. The sol gel technique has been most used because it allows for low temperature synthesis, with excellent purity and simple control of the reaction conditions 6 .…”
Section: Introductionmentioning
confidence: 99%